Turismo, tecnologia e cidades criativas [recurso eletrônico: aplicativo Artur: assistente de rotas turísticas para deslocamentos, a pé, pela cidade do Recife-PE - Santos, Antonio Geraldo Ferreira dos (2021)
This study proposes the development of the application Artur - Assistant of Tourist Routes - a digital tool for smartphones that helps tourists with information and entertainment during their walks, on foot, through the city of Recife/PE. In this context, the present research sought to develop an application based on current digital information and communication technologies (ICTs) and on the investigation of concepts such as creativity and innovation. We also sought to analyze the demands of the tourism sector for digital products/services and propose innovative solutions to maximize tourist experiences in urban areas. In its methodology, this work carried out a survey with a group of users in order to verify their habits in the use of smartphones, what is the application of the internet in tourist planning and leisure activities, what digital tools are used in tourism practices and how these tools (applications, websites, platforms) affect the visitation process. In view of this, a prototype was developed for the Artur application, in order to simulate its main functions, among them, the creation of tourist routes from pre-established themes, a geolocation system, a support of information about tourist attractions in the surroundings. and a dynamic of interaction through games, music and curiosities about the visited environment. The tool aims to expand the exploration of the visited place and add new experiences to tourist activities in urban centers.